PENGARUH KOMUNIKASI, MOTIVASI KERJA DAN PENGALAMAN KERJA TERHADAP DISIPLIN KARYAWAN PT. BANK PEMBANGUNAN DAERAH BALI KANTOR PUSAT - Dessy, Putu Nika Adnya; Wibawa, I Made Artha (E-Jurnal Manajemen, 2015)
Discipline is a condition that shows the values ??of obedience, obedience, loyalty, peace, order and order. This study aims toidetermine theieffect of communication, motivation and workiexperience to discipline employees simultaneously and partial, as well as the dominant variable effect on employee discipline. This research was conducted at PT. Bali Regional Development Bank Headquarters. 125 respondents were sampled, using simple randomisampling method. Dataicollected throughiobservation, interviewsiandiquestionnaires. The analysisitechnique usediis multipleilinear regression analysis. The resultsishowed that, communication, motivation and work experience simultaneously and partially an effect on employee discipline. For further research should add other variables could be used as study variables such as loyalty, morale and work environment.
Keywords: komunikasi; motivasi kerja; pengalaman kerja dan disiplin